Energy management in ports and its impact on port sustainability and regional competitive advantage - Li, Jianni (2018)
Ports have evolved remarkably through the years, but energy management in ports has always been a growing concern. Stakeholders are putting more efforts to promote energy management by adopting latest green energy innovations (such as uptake of renewables and power generation) in ports to maximize profits and minimize costs as they have realised the importance of reducing the emission of GHG so as to obtain energy efficiency in port. This research focuses on the aspect of energy management in Next Generation Port (NGP), its impact on sustainability and its competitive advantage. Port of Singapore is the unit of analysis and further study will be conducted on what drives it into becoming a NGP, together with how co-regional development is being enhanced in the process. Both primary and secondary research will be conducted in this paper. Through secondary research, different literatures and research papers were collected and analysed to gain in-dept understanding of the different energy strategies deployed worldwide. Different industry professionals that play important role in Singapore NGP and regional development have also given their valuable inputs in survey and interviews to substantiate the primary research. The characteristics of NGP and regional development will be first analysed to ensure ports are ‘smart’ in deploying energy innovations to boost their social, economic and spatial aspects. Following that, the importance of the relationship between energy management and infrastructures are examined to ensure sustainability in port. Next, information on energy management strategies such as the deployment of green innovations (solar power, electricity) and green initiatives and policies are collected to study on their feasibility in different kind of ports worldwide. The information collected is further used to study the port of Singapore. At last, a framework on four key aspects of energy management was recommended to promote better energy management and co-regional development in Singapore port, while maintaining its competitive advantage. All in all, this study has shown that port of Singapore has an optimistic outlook in their energy management. The well-connected network of green infrastructures, with the use of green innovations and technologies, have revealed that Singapore will be able to fulfil the concept of a NGP in terms of energy management and further enhances its co-regional development.